MANTID FAUNA OF CHANDOLI NATIONAL PARK, MAHARASHTRA, INDIA - Y. J. KOLI; G. P. BHAWANE (The Bioscan, 2011)
A year-long survey was conducted to assess the mantid species assemblage in various natural and anthropogenic habitats of Chandoli National park. Total of 11 Mantid species belonging to 11 genera, 7 subfamilies and 3 families were recorded. The family Mantidae (7 species) was found to be dominant in the study region, followed by families Hymenopodidae and Empusidae (2 species each).